Gambaran Tingkat Kepuasan Mahasiswa Profesi Ners Terhadap Perkuliahan Daring Saat Pandemi Covid-19 - Amri, Cessy Oktarina (Universitas Aufa Royhan, 2022)
Nurse profession practitioners during Covid-19 pandemic must require nurse student's proffesion to do an online learning system. The purpose of this study is describing satisfaction level among nurse student's profession to online learning system during Covid-19 pandemic. This study was using a decription design. This study was be held in Nursing Faculty of Riau University with 84 sample which was using simple random sampling technique with took focus on inclusion criteria. The measurement of this study was using questionnaire and already being examinated by validity test and reliability test. The analysis was using univariat analysis. This study showed that the the most age of respondents were 23 years old (64,3%) and the majority of gender was female (89,3%). The result of this study showed that satisfaction student's level (61,9%) felt quite satisfied. The level of satisfaction based on tangible dimension were less satisfied (48,8%), based on reliability dimension were quite satisfied (58,3%), based on responsiveness dimension were less satisfied (45,2%), based on assurance dimension quite satisfied and after that based on student's satisfaction of emphaty dimension were quite satisfied (70,2%). The result of this study conclude that the average among students felt quite satisfied with online learning system among nurse profession practitioners. The level of student satisfaction can be increased by providing sufficient internet quota, giving a study method that able to increase the skill in the real scope of nursing, mentoring process with the right and on time schedule, helping students that find any difficulties then giving enough time to do self assignments with enough time.